Initial results from solenoid-free plasma start-up using Transient CHI on QUEST. (14th September 2018) - Kuroda, K; Raman, R; Hanada, K; Hasegawa, M; Onchi, T; Ono, M; Nelson, B A; Jarboe, T R; Nagata, M; Mitarai, O; Nakamura, K; Idei, H; et al.
Abstract: Initial results from the recently implemented transient coaxial helicity injection (CHI) system on QUEST are reported. QUEST uses a new CHI electrode configuration in which the CHI insulator is not part of the vacuum boundary, making this configuration easier to implement in fusion reactors. Experimental results show that transient CHI startup in this alternate electrode configuration is indeed possible. Reliable gas breakdown was achieved, and toroidal currents up to 45 kA were generated.